Model-Model Pembelajaran - Marde Christian Stenly Mawikere (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2022)
Learning and learning models are always changing according to the times and changes in social transformation because time always points forward. Even so, the nature and existence of learning cannot be separated from students, teachers and the context. In principle, learning is a process of interaction between students and teachers and the entire context of the existence and life of students and teachers. Learning is also a process that is directed so that learning outcomes can be achieved as well as a behavioral process obtained through a variety of learning experiences. That's why it is important for a teacher to prepare everything related to the learning that will be carried out for students. The preparation starts from Learning Plans or Designs, Learning Models to Learning Evaluations. The substance of all that is what and how to direct students in the learning and learning process so that students will be active, fun, and meaningful when learning. Thus, learning models are important factors that must be identified, applied and developed in supporting a learning process.AbstrakModel-model Belajar dan pembelajaran selalu mengalami perubahan sesuai perkembangan zaman dan perubahan transformasi sosial oleh karena waktu selalu mengarah ke depan. Sekalipun demikian, hakikat dan keberadaan pembelajaran tidak terlepas dari murid, guru dan konteksnya. Pada prinsipnya, pembelajaran merupakan proses interaksi antara murid dan guru serta seluruh konteks keberadaan dan kehidupan murid dan guru. Pembelajaran juga merupakan suatu proses yang diarahkan supaya capaian pembelajaran dapat dicapai sekaligus merupakan proses perilaku yang diperoleh melalui ragam pengalaman belajar. Karena itulah penting bagi seorang guru untuk mempersiapkan segala sesuatu berkaitan dengan pembelajaran yang akan dilaksanakan bagi para murid. Persiapan tersebut mulai dari Rencana atau Desain Pembelajaran, Model-Model Pembelajaran sampai dengan Evaluasi Pembelajaran. Substansi dari semua itu adalah seperti apa dan bagaimana mengarahkan murid dalam proses belajar dan pembelajaran supaya para murid akan aktif, menyenangkan, dan bermakna pada saat belajar. Dengan demikian model-model pembelajaran adalah faktor penting yang harus diidentifikasi, diterapkan dan dikembangkan dalam mendukung suatu proses pembelajaran.